Health promoting settings in primary health care - "hälsotorg": an implementation analysis - Wallenberg Lovisa; Olander Ewy; Mahmud Amina; Haglund Bo JA (BMC, 2010)
Abstract Background Sweden, like many other western countries, faces increasing rates of lifestyle related diseases and corresponding rise in costs for health care. To meet these challenges, a number of efforts have been introduced at different societal levels. One such effort is "Hälsotorg" (HS). HS is a new health promotion setting that emerged in collaboration between the Swedish County Councils and Apoteket AB, a state-owned pharmacy company. HS's overall aim was to improve population health and facilitate inhabitants' responsibility for self-care. A new National Public Health Policy, introduced in 2008, emphasizes more focus on individual's needs and responsibility as well as strong need for county councils to provide supportive environment for individual-centred health services and increased health literacy among the population. In light of this policy, there is a need to examine existing settings that can provide supportive environment for individuals at community level. The aim of this study was to explore HS's policy implementation at local level and analyse HS's activities, in order to provide a deeper understanding of HS's potential as a health promoting setting. Methods Materials included a survey and key documents related to the development and nature of HS on local and national levels. A policy analysis inspired by Walt and Gilson was used in data analysis. In addition, an analysis using the principles of health promotion in relation to HS policy process and activities was also carried out. Results The analysis illuminated strengths and weaknesses in the policy process, its actors, contextual factors and activities. The health communication approach in the analysed documents contained health promoting intentions but the health promoting approach corresponding to a health promoting setting was neither apparent nor shared among the stakeholders. This influenced the interpretation and implementation of HS negatively. Conclusions The analysis indicates that HS has potential to be a valuable health promotion setting for both population and individuals, given the strong intentions for a health and empowerment building approach that is expressed in the documents. However, for a more sustainable implementation of HS, there is need for an in- depth understanding of the health promotion approach among HS stakeholders.